The effect of laying down posture while using smartphone among school children in Nakhon Si Thammarat, Thailand - Uraiwan Madardam; Siriluk Veerasakul; Shamsul Bahri Mohd Tamrin; Jittaporn Mongkonkansai (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. Lots of children use the smartphone in lying down posture that is unappreciated posture. The postures of children while using a smartphone affect their musculoskeletal pain and can enhance Musculoskeletal Disorders (MSDs). Objective. To study the effect of lying down posture while using smartphone among school children in Nakhon Si Thammarat, Thailand. Materials and methods. This survey study employed a Descriptive Cross-Sectional Design. The population was Grade 1-6 students studying in a primary school in Nakhon Si Thammarat. There were 122 samples selected based on the Volunteer Sampling Technique under the written consent of the students' guardians. The research instruments employed in this study were: 1) Questionnaire adapted from Nordic Musculoskeletal Questionnaire asking musculoskeletal symptoms, 2) Posture Assessment using Kinovea Software to measure the angles of the muscle and postures during photo and video shooting of the smartphone users. The data were analyzed using descriptive statistics while Chi-square and Mann-Whitney U tests were used to test the mean differences. Results. There is a significant difference at p<0.05 level in mean angles of the neck, trunk, shoulder, and lower arms when using smartphones in supine and prone postures. The correlation between smartphone usage postures and musculoskeletal symptoms at the head/neck, trunk, and upper arm are found significantly different at p<0.05 level. The statistically significant difference at p<0.05 level is also found in the differences of age, length of smartphone ownership, position when using smartphone, and length of a smartphone usage in lying down positions. Conclusion. Smartphone usage in lying down positions of the participants can cause musculoskeletal pain especially in prone posture. It is recommended that guardians or relevant sectors have greater attention to smartphone usage among children to prevent their long-term musculoskeletal problems.